Job characteristics, working conditions and job stress on academicians well-being in open distance learning environment - Jeniza, Jamaludin (2023)
The up surging of academicians’ job stress and the challenge to maintain job characteristics such as job demand, job autonomy, social support, and combined with the change of working conditions of academicians in an open and distance learning setting is causing severe decline of academicians’ well-being. The presence of open and distance learning has changed the conventional nature of work in education to digital learning. This study aims to examine the relationship between job characteristics (job demand, job autonomy, social support), working conditions, and job stress on academicians’ well-being. The study also examined the role of job stress as mediator variable. A quantitative approach via survey was employed. Respondents were 200 academicians from five Open and Distance Learning universities in Malaysia namely Open University Malaysia, Wawasan Open University, Asia e University, Al-Madinah International University and the Global University of Islamic Finance. Data analysis was performed using partial lease squares structural equation modelling (PLS-SEM). The research findings revealed significant influence of job demand, job autonomy, working conditions, on academicians’ well-being. However, social support did not influence academician’s well-being. Furthermore, the finding revealed job stress as a significant mediator within the open and distance learning context. There are several positive research implications where open and distance learning universities implement wellness and stress management practices to mitigate job stress among academicians. These include redesigning the academic’s job to increase support resources and issues such as developing policies, responsibilities training, and online setting. Moreover, the social context theory in this research contributes to the literature on academicians’ well-being in the open and distance learning setting. Many private and public universities have moved toward the open and distance learning which may lead to a larger sample size. Future studies is needed to improve the results of the data analysis and more empirical research can be conducted.